TKETELADANAN GURU DALAM PERSPEKTIF PANDANGAN AL-QUR’AN DAN AL-HADIST MELALUI IMPLEMENTASI KURIKULUM 2013 - Jajuli Jajuli; Sukarso Ghrazianendri (Fakultas Agama Islam Universitas Wiralodra, 2019)
This article aims to describe the importance of teacher modeling in the view perspective of the Qur'an and the haditS through the implementation of Curriculum 2013. The teacher modeling is the main key to be the success of education activities by following the globalization challenges. In education, teachers act as an educator, motivator, inspiration, and guidance in developing the attitudes, skills, and knowledge. Exemplary concept based on the Qur'an and Al-Hadith urgent presence for the curriculum in 2013 itself can be integrated which leads directly corresponds to the objectives of the National Education which is to be a man who is faithful and devoted to God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible.